A RAS inhibitor reduces allergic airway remodeling via regulating IL-33-derived type 2 innate lymphoid cells. (21st October 2021) - Tezuka, Toshifumi; Azuma, Masahiko; Ogawa, Hirohisa; Kondo, Mayo; Uehara, Hisanori; Aono, Yoshinori; Hanibuchi, Masaki; Nishioka, Yasuhiko
Abstract: Purpose: IL-33 is known to induce corticosteroid-resistant eosinophilic inflammation and airway remodeling by activating type 2 innate lymphoid cells (ILC2s). Although the RAS signal pathway plays an important role in IL-33-induced ILC2s activation and airway remodeling, it is not known if RAS inhibitors are effective against refractory asthma. We examined the effects of the RAS inhibitor XRP44X in refractory asthma. Methods: RAS activity were examined by BAL fluid and T-cells isolated from spleen cells in Dermatophagoides pteronyssinus (Dp)-sensitized/challenged acute allergic airway inflammation model. A chronic allergic airway inflammation mouse model was generated by challenged with Dp. XRP44X and/or fluticasone were administrated nasally to different experimental groups. The effects of nasal simultaneous administration of XRP44X or fluticasone were assessed in mice administrated with IL-33 or Dp. Results: RAS activity in CD4 + T cells stimulated by Dp were suppressed by XRP44X. Although fluticasone and XRP44X only improved allergic airway inflammation in mice, XRP44X in combination with fluticasone produced further improvement in not only eosinophilic inflammation but also bronchial subepithelial thickness. XRP44X suppressed IL-5 and IL-13 production from ILC2s, although this effect was not suppressed by fluticasone. IL-33-induced airway inflammation resistant to fluticasone was ameliorated by XRP44X via regulating the accumulation of lung ILC2s. Conclusion: The RAS signal pathway plays a crucial role in allergen-induced airway remodeling associated with ILC2s. XRP44X may have therapeutic potential for refractory asthma.